Orthotic Insoles Improve Gait Symmetry and Reduce Immediate Pain in Subjects With Mild Leg Length Discrepancy - Menez, Charlotte; L'Hermette, Maxime; Coquart, Jeremy (Frontiers in Sports and Active Living, 2020)
Background: Mild leg length discrepancy can lead to musculoskeletal disorders, however the magnitude starting from which leg length discrepancy alters the biomechanics of gait or benefits from treatment interventions is not clear. Research question: The aim of the current study was to examine the immediate effects of orthotic insoles on gait symmetry and pain on mild leg length discrepancy according two groups of the leg length discrepancy (i.e., LLD ≤ 1 cm vs LLD > 1 cm). Methods: Forty-six adults with mild leg length discrepancy were retrospectively included and classified in two groups (GLLD≤1cm or GLLD>1cm). All subjects underwent routine 3D gait analysis with and without orthotic insoles. The symmetry index was calculated to assess changes in gait symmetry between the right and left limbs. Pain was rated without (in standing) and with the orthotic insoles (after 30 minutes of use) on a visual analogue scale. Results: There was a significant improvement in the symmetry index of the pelvis in the frontal plane (p = 0.001) and the ankle in the sagittal plane (p = 0.010) in stance with the orthotic insoles independent from the group. Pain reduced significantly with the orthotic insoles independently from the group (p < 0.001). Significance: Orthotic insoles significantly improved gait symmetry in the pelvis in the frontal plane and the ankle in the sagittal plane, as well as pain in all subjects (both LLD ≤ 1 cm and LLD > 1 cm) suggesting that it may be appropriate to treat even mild leg length discrepancy.